La gestion intégrée des zones côtières et le droit de l’urbanisme littoral en France - Xavier Braud (VertigO)
Integrated management of the coastal zones (IMCZ) and urban planning of the littoral law are linked by their great proximity of their object. However, only the second constitutes a legal tool and both thus have a very different nature. The IMCZ has, unlike the urban planning of the littoral law, no normative vocation. It is only in the last few years that we find its trace, accidentally, in legal texts, as a goal, a reference, but not generating substantive laws. So that today the implementation of public policies, inspired by the IMCZ, can only remain framed by the urban planning of the littoral law. This implementation requires the intervention of administrative decisions that can be subjected to a control regards to the standards of urban planning of the littoral law. These, it is necessary to raise it, should be considered as the same logic of IMCZ before the term existed, integrating in particular the concerns of protection and development of economic activities connected to the coast. From then on, we can wonder if the IMCZ is so innovative as we are generally willing to assert it. Would not it have acquired in the course of its assimilation by the administrative and political speeches another purpose ? Of a scientific management logic, it tends to become a public policy which could eventually impose important modifications on the urban planning of the littoral law in the direction of an important weakening and a considerable dilution of the concerns of coast protection.